MEDIA POHON BERHITUNG UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA SEKOLAH DASAR - Siti Kurniati; Melkyanus Bili Umbu Kaleka; Maria Alberta Liza Quintarti (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2020)
Learning from home is a step taken in dealing with conditions that occur due to Corona Virus 19. One of the methods applied is to form study groups with varying frequency of teacher visits. This of course requires energy and time so that learning is more effective and efficient. Lack of mentoring by the teacher causes students to spend time playing. Through real work lectures, students of the Elementary School Teacher Education study program developed an innovative learning media, namely a counting tree to increase the learning activities of grade 1 elementary school students. This solution is taken so that students can fill their learning time while playing. The expected results after this service activity, teachers and parents can use learning media to guide students at home, and enable teachers to innovate in developing learning media.